CHARACTERISTICS OF INDICATORS IN PRIVATE CAPITAL VALUATION OF JOINT STOCK COMPANIES IN UZBEKISTAN - Khurshid Kgudoykulov (Antis Publisher, 2024)
in the article, the indicators that affect the assessment of the capital value of the joint-stock company are analyzed based on the value of the calculated assets, private capital values from 2015 to 2019. In particular, the main attention is paid to the factors affecting the capital value of joint-stock companies in our country